British Standard Methods of test for : Electrohydraulic proportional control valves - British Standards Institution, author 8096 (London : British Standards Institution, 1986)
Production acceptance and type (or qualification) tests. Applicable to 2-, 3- and 4-way flow control valves and to 2-way pressure control valves.